2021
DOI: 10.3390/genes12020184
|View full text |Cite
|
Sign up to set email alerts
|

The Tomato Interspecific NB-LRR Gene Arsenal and Its Impact on Breeding Strategies

Abstract: Tomato (Solanum lycopersicum L.) is a model system for studying the molecular basis of resistance in plants. The investigation of evolutionary dynamics of tomato resistance (R)-loci provides unique opportunities for identifying factors that promote or constrain genome evolution. Nucleotide-binding domain and leucine-rich repeat (NB-LRR) receptors belong to one of the most plastic and diversified families. The vast amount of genomic data available for Solanaceae and wild tomato relatives provides unprecedented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 90 publications
2
24
0
Order By: Relevance
“…In detecting association, we included the 2-kb regions flanking both sides of the genes. First, we compared hotspots against R genes, which are known to reside in recombination hotspots ( Nieri et al 2017 ; Andolfo et al 2021 ), and observed a significant overlap (Fisher’s exact test; P = 3.38×10 −17 ). Afterward, we computed the overlap between hotspots and the selective sweeps or regions with reduced nucleotide diversity previously reported by Lin et al (2014) .…”
Section: Resultsmentioning
confidence: 99%
“…In detecting association, we included the 2-kb regions flanking both sides of the genes. First, we compared hotspots against R genes, which are known to reside in recombination hotspots ( Nieri et al 2017 ; Andolfo et al 2021 ), and observed a significant overlap (Fisher’s exact test; P = 3.38×10 −17 ). Afterward, we computed the overlap between hotspots and the selective sweeps or regions with reduced nucleotide diversity previously reported by Lin et al (2014) .…”
Section: Resultsmentioning
confidence: 99%
“…On average, a slightly higher number of CNLs compared to TNLs was identified in most Cucurbita assemblies. A similar CNL\TNL ratio was found in Solanaceae (Di Donato et al 2017;Andolfo et al 2021), while the Brassicaceae and Fabaceae contain from twofold to sixfold more TNL than CNL genes (Guo et al 2011;Kang et al 2012). Surprisingly, the Cucurbita RNL (also known as helper) genes varied from ~ 18 to ~ 6% of the full NLR gene complement (Suppl.…”
Section: Discussionmentioning
confidence: 65%
“…Our results showed that of the 17 reference NLRs that have been cloned and characterized in species of the genus Solanum and that were also used in this study, 8 of them are present in shared orthogroups with coffee (Supplementary Table 2 and Supplementary Table 8), being 1 TNL ( Gro1-4 ) and 7 CNL ( Hero, Prf, Rpi-blb1, Rx2, Sw-5, Tm-2a, Tm-2 ). These genes have been found to be involved in resistance to a diverse group of pathogens including viruses, oomycetes, bacteria and nematodes (Bendahmane et al, 2000; Van Der Vossen et al, 2003; Paal et al, 2004; Andolfo et al, 2021). In total, 46 orthogroups were shared between coffee and solanum indicating that these orthologs were probably present before the speciation of these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In all three coffee species, a set of orphan genes and orthogroups that share NLRs within the same species were detected. In tomato, 45 of ~320 NLRs sequences are more similar to each other than to any other sequences compared (Andolfo et al, 2021) and orthogroups that share NLRs within the same species of Solanum are attributed to duplication events that generate different gene repertoires and result in species-specific subfamilies (Seo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation